Institutionalizing Evidence-Informed Priority Setting for Universal Health Coverage: Lessons From Indonesia - Manushi Sharma MBA; Yot Teerawattananon MD, PhD; Alia Luz MSc; Ryan Li PhD; Waranya Rattanavipapong MSc; Saudamini Dabak MA (SAGE Publishing, 2020)
Planning and administering Universal Health Coverage (UHC) policies involve complex and critical decisions, especially in resource-scarce and densely populated settings such as Indonesia. Increasing investments alone do not ensure success and sustainability of UHC, and defining priorities is imperative. In 2013, Indonesia formally embarked on its journey of institutionalizing priority setting with technical assistance from the International Decision Support Initiative (iDSI), which is a global network of organizations in pursuit of evidence-based priority setting. This article provides a perspective for countries in pursuit of institutionalization of evidence-informed policy setting systems and sheds light on the factors conducive to the development of health technology assessment (HTA). It explores the main actors and the context of priority setting in Indonesia and articulates strategies and key outcomes and impact using the theory of change (ToC).